Petal anatomy of four Justicia (Acanthaceae) species - Ahmad Juhari, Muhammad Amirul Aiman; Talip, Noraini; Che Amri, Che Nurul Aini; Abdul Rahman, Mohamad Ruzi (AIP Publishing, 2013)
Comparative anatomical study on flower petals was studied in four selected Justicia species from Peninsular Malaysia, i.e. J. comata (L.) Lam., J. carnea Lindl. J. betonica Linn. and J. procumbens L with the objective to provide useful data for species identification and differentiation within the genus of Justicia. Methods used in this study are mechanical scrapping on the leaf surfaces and observation under light microscope. Finding in this study has shown that all species are sharing similar type of anticlinal walls pattern, which is sinuous pattern. Two or more type of trichomes is present in all species studied and this character can be used to differentiate Justicia species. Simple multicellular trichomes are found to be present in all species studied. Justicia betonica can be isolated from other species by the existence of cyclo-paracytic stomata on the petal surfaces.